Laser induced damage threshold (LIDT) of β-barium borate (BBO) and cesium lithium borate (CLBO) – Overview. (May 2022) - Turcicova, H.; Novak, O.; Muzik, J.; Stepankova, D.; Smrz, M.; Mocek, T.
Highlights: BBO and CLBO crystals are preferred for deep ultraviolet generation. Overview given of LIDT measurements of BBO and CLBO. LIDT is the crystallinity level and purity dependent. Pulse duration is a factor substantially affecting LIDT. Abstract: Published data of laser induced damage thresholds (LIDT) of nonlinear BBO and CLBO crystals, which are used for the generation of deep-ultraviolet radiation, are collected and plotted against laser pulse duration. The LIDT measurement techniques are briefly described and their relevance relative to the intended application of the crystal is discussed. The intrinsic and extrinsic factors affecting the evolution of the LIDT are reported. Our own experience with the LIDT of BBO and CLBO crystals in the fifth harmonic generation (FiHG) process is presented. Lowering of the LIDT for crystals with antireflection coatings is treated.